2016
DOI: 10.1021/acs.jpcc.6b07328
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Thermodynamics and Kinetics for Coalescence of Two-Dimensional Nanoislands and Nanopits on Metal (100) Surfaces

Abstract: Postdeposition coalescence or sintering of pairs of lowstrain two-dimensional nanoislands and nanopits on unreconstructed metal (100) surfaces is typically mediated by diffusion along step edges, and is highly sensitive to the associated kinetics. Thus, for selected systems, we provide an ab initio density functional theory (DFT) level description of both system thermodynamics and kinetics. Specifically, we assess lateral pair and trio interactions both conventionally with adatoms at 4-fold hollow adsorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 84 publications
1
67
0
Order By: Relevance
“…It is generally accepted that cluster diffusion is mediated by periphery diffusion (PD), also described as edge diffusion, of adatoms along the steps at the periphery of the cluster. The STM studies prompted extensive atomistic lattice-gas modeling starting in the 1990's of epitaxial cluster diffusion [4][5][6][7][8][9][10][11] and of related reshaping phenomena [12][13][14][15][16][17][18][19]. This work supplemented limited earlier studies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that cluster diffusion is mediated by periphery diffusion (PD), also described as edge diffusion, of adatoms along the steps at the periphery of the cluster. The STM studies prompted extensive atomistic lattice-gas modeling starting in the 1990's of epitaxial cluster diffusion [4][5][6][7][8][9][10][11] and of related reshaping phenomena [12][13][14][15][16][17][18][19]. This work supplemented limited earlier studies [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…E eff also reflects thermodynamic parameters determined by adatom interactions, particularly the formation energy, E form , to create a step edge atom from a kink atom. It was previously suggested that long-range cluster diffusion is limited by creation of edge atoms through their extraction from the core of the cluster or "core breakup" [1,20], so that E eff = E e + δ + E form [19]. This perspective is consistent with the predictions of the mesoscale continuum Langevin theory where the activation energy for cluster diffusion corresponds to that for mobility of edge atoms, E PD , where σ PD ~ exp[-E PD /(k B T)] with E PD = E e + δ + E form [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]5,6 Note also that reshaping of 2D epitaxial clusters and pits, or 3D clusters and voids in bulk crystals, is equivalent on the macroscale, 16 but not on the nanoscale. 11,12 The size-dependence of diffusivity of supported metal nanoclusters was also found to deviate from macroscale predictions. [17][18][19][20][21][22] Refined continuum treatments with multiple order parameters might describe such anomalous scaling of diffusion.…”
mentioning
confidence: 97%
“…6 Differences occur when linear nanocluster sizes, L, decrease below various characteristic lengths. [1][2][3][9][10][11][12] For L < L k , the characteristic separation between kinks on close-packed step edges, 2D clusters become effectively faceted and reshaping is controlled by inhibited nucleation of new edges. 9 Similar anomalies have been discussed for 3D nanoclusters, but here facets can be macroscopic and nucleation of new layers becomes prohibitive above nanoscale.…”
mentioning
confidence: 99%
“…For metal(100) systems, one generally expects 2NN pair attractions and bent trio repulsions to be ~10% of the strength of NN interactions (and weaker longer range pair and many-body interactions also exist). [28][29][30] However, in Appendix B, we argue that our simpler model with just NN attractions recovers the appropriate near-square equilibrium shape of clusters at least for Ag(100). The actual hopping dynamics in metal(100) systems is also more complicated than our prescription, as has been determined by a comprehensive DFT analysis of energetics at both the initial site and the transition state for hopping for general step edge configurations.…”
Section: A Model Details and Kmc Simulation Of Cluster Diffusionmentioning
confidence: 86%